Determination of porosity of clay rocks in cased oil and gas wells using radioactive and acoustic logging - Bondarenko, M. S.; Karmazenko, V. V.; Kashuba, G. A.; Kulik, V. V. (Geofizicheskiy Zhurnal, 2010)
Traditional and new methods of determination of porosity of clay rocks in the cased holes by means of radioactive and acoustic logging are considered. By an empirical way the approximate invariance of double differential parameter of gamma-ray logging for a given borehole section is shown in case of measurements in an open hole and through casing. By logging data of oil and gas boreholes of the Dnieper-Donets depression examples of determination of porosity in the cased holes by the various methods, as well as an example of complex use of porosity on radioactive logging and acoustic logging for solution a specific problem of petroleum geophysics have been presented.